Haemangioma of Infancy: Two Case Reports with an Overdose of Propranolol - Janmohamed, S.R. (S. Karger AG, 2011)
An 8-week-old infant was treated with oral propranolol for a haemangioma of infancy. The standard dose (according to protocol) is 2 mg/kg/day but, because of a mistake by the pharmacist, the child was treated with 8 mg/kg/day without any side effects (pulse, blood pressure and glucose stayed normal).